Characterization parameters and mechanical response in diatomaceous soil depending on species (2017)
"Diatomaceous soil deposits around the world have become an special research focus considering some non conventional results (high values) related with shear strenght parameters, specially internal friction angle Q' (Diaz, 1992)(Cheng, 2007), even when there are high contents of organic matter or fine particles. The actual state of art report high values but do not determine the Diatom specie asswated with that result, and even less compare the results obtained in different places of the world specifying the native specie. This project tends preciselly to analyze the effect of speoe in previous mentioned parameters specially in those related with characterization, compressibility, shear strenght and load capacity... The investigation limits extended until two Diatoms species (Aulacoseira granulata Colombian ongin and the Centric Coscinodiscus Mexican ongin) tending to identify the variation in soil resistance parameters, behavior in the one dimensional Consolidation process, and even in the characterization criteria, based on species changes2. -- Tomado del resumen.